Clinical Evaluation of Li Brush Endometrial Samplers for Diagnosing Endometrial Lesions in Women With Intrauterine Devices - Han, Lu; Ma, Sijia; Zhao, Lanbo; Liu, Yu; Wang, Yiran; Feng, Xue; Zhang, Kailu; Wang, Lei; Wang, Li; Yin, Panyue; Liang, Dongxin; Hou, Huilian; et al. (Frontiers in Medicine, 2020)
Background: For women with intrauterine devices (IUDs), it is difficult to sample the endometrium when abnormal uterine bleeding occurs or when regular screening of endometrial cancer is proposed. The purpose of this study is to evaluate the validity of endometrial sampling using Li Brush in IUD users. Methods: This study was a prospective cohort study and conducted in two parts. Part Ⅰ was to assess the impact of Li Brush on the position of IUDs. Transvaginal ultrasound was used to locate IUDs before and after sampling. Part Ⅱ was to explore the diagnostic accuracy of Li Brush in detecting endometrial lesions. IUD users with irregular uterine bleeding were recruited in the IUD group and IUD non-users who arranged for dilatation and curettage (D&C) were recruited in the control group. The endometrium was sampled by Li Brush for cells and by D&C for tissues in both groups. The satisfactoriness of sampling and validity of Li Brush were evaluated. Results: Seventeen cases in part Ⅰ confirmed no significant difference in the position of IUDs before and after sampling (p=0.20). 112 IUD users and 139 IUD non-users were recruited in part Ⅱ. Li Brush achieved 94.64% and 92.09% satisfactory sampling rates in the IUD group and control group, respectively, without statistically significant difference between the two groups (p=0.42). The Sensitivity and specificity of Li Brush for detection of endometrial lesions in IUD group were 95.35% and 87.76% respectively. Conclusions: Li Brush used for endometrial biopsy did not affect the position of IUDs and had high yield of satisfactory samples and good validity for endometrial diagnoses. It was feasible to screen endometrial lesions by Li Brush for women with IUDs.